Factors Affecting Employee Performance at PT. Indomarco Prismatama Jakarta - Suryanto suryanto; Markonah Markonah (Perbanas Institute, 2023)
This research aims to analyze the factors that influence the work environment, work discipline and work motivation on employee performance at PT Indomarco Prismatama. The data analysis methods used are Validity Test, Reliability Test, Classical Assumption Test, Determination Coefficient Test, Statistical Test, and multiple linear regression analysis. And the data used in this research is primary data obtained from distributing questionnaires to employees at PT Indomarco Prismatama. The sample collection technique in this research was non-probability purposive sampling, a saturated sample with a total of 70 permanent employees at PT Indomarco Prismatama. The type of research used is a descriptive analysis method with a quantitative approach assisted by SPSS version 18 data processing tools. The research results show that the work environment has a positive effect on employee performance; Work discipline has a positive effect on employee performance; and work motivation has a positive effect on employee performance. So it is recommended to PT Indomarco Prismatama to improve the work environment, work discipline and work motivation.